Pengaruh Ekstrak Patikan Kebo (Euphorbhia hirta Linn) Terhadap Serangan Hama Daun Sawi - M Indar Pramudi; Eka Febrianti; Helda Orbani Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Plant Pest Organisms that often attack mustard are Tritip caterpillar (Plutella xylostella L), armyworm (Spodoptera litura F), growing point caterpillar (Crocidolomia binotalis Zel), common pests that often attack mustard, namely Leaf Grasshopper (Phyllium pulchrifolium), Nezara viridula L, and Chrysodeixis chalcites. One of the environmentally friendly pest control techniques is the use of pesticides derived from plants which are commonly called biopesticides. Patikan kebo (Euphorbia hirta L) was known to contain antibacterial active compounds that can be used as organic herbicides. This study used patikan kebo extract with several concentrations to suppress the attack of mustard leaves destroying pests. The research took place in a vegetable growing area and was carried out for 40 days from sowing to harvesting. The research was conducted using an experimental method. The results of this study showed that all treatments of patikan kebo extract were able to suppress the attack of mustard leaf pests and the use of a very significant concentration was found in (7.5 ml) with the lowest attack intensity of 4.79%.